A Simple Test of Spatial Autocorrelation for Centered Variables - Mur, Jesús (2021)
We present a simple test of spatial autocorrelation based on the skedastic structure of the spatial series. Its distribution function is known for all sample sizes. Moreover, it is very simple to obtain, specially in a case of small samples where the new GQsp test has great power, higher than other alternatives existing in the literature.